The Kinetics of the Hydrolysis of Trans-K[Cr(ox)z(H20)2] .3H2O - Abdullah, Mohamad Ali; Aztz, Bakhtyar Kamal (Sulaimani Journal for Pure and Applied Sciences, 2007)
In the present work, the kinetics of the hydrolysis of the complex Trans-K[Cr(ox)2(H2o)z]'3Hzo have been srudied in aqueous media at (pH:4.i,5.1;5.6 and 6.3) _(trr:0-4 NaNO3)' The hydrolysis rate was found to be acid dependent and show a linear increase witn [U*1-'. The activation parameters for the reactions are (Ear45.77 kJ;;l',;ft*, =+:.tS kJ mol-r and ASlr = -Zna J mo1-1) and (Eaz=81'21 kJ mol' ilHi;=tg.59 r.j *or t and ASf2 : -i:.az J mol-t). The observed rate constants are in good agreernent with that reported by Kallen and Hamm for the anation of {Cis-[Cr(ox)z6zOh]-]'
Keywords: Cr(lII) complex; kinetic lability; hydrolysis